Invitation to a beheading - Nabokov, Vladimir Vladimirovich, 1899-1977 (Vintage International (Series), 1989)
In an unnamed dream country, the young man Cincinnatus C. is condemned to death by beheading for 'gnostical turpitude, ' an imaginary crime that defies definition. Cincinnatus spends his last days in an absurd jail, where he is visited by chimerical jailers, an executioner who masquerades as a fellow prisoner, and by his in-laws, who lug their furniture with them into his cell.